Case 3828: The family name of the pearl oysters: Proposal to remove the homonymy of Margaritidae Blainville, 1824 (Mollusca, Bivalvia) with Margaritidae Thiele, 1924 (Mollusca, Gastropoda), by amending the latter to Margaritesidae - Bieler, Rüdiger; Bouchet, Philippe (Bulletin of Zoological Nomenclature)
Noticed in BZN 77: 113 on 30 December 2020.